STRATEGI PENGEMBANGAN HUTAN RAKYAT BERSERTIFIKAT DESA DUKUHDALEM KECAMATAN JAPARA KABUPATEN KUNINGAN JAWA BARAT Studi Kasus : Kelompok Tani Mekarsaluyu II - Nugraha, Yogha Adhie; Hendrayana, Yayan; Deni, Deni (Wana Raksa, 2023)
The problem with certified community forests is management problems, government policies that have not been optimal regarding certified community forests (There is a policy of P.85 / Menlhk / Setjen / Kum.1 / 11/2016) What used to be a certified community forest is mandatory now is not because for uncertified community forests, they can use transportation notes for their wood products), certified forest farmer groups are less in looking for opportunities, management is still traditional, and the existence of certificates does not guarantee easy selling of their wood products. For this reason, the method used in this research is to use the SWOT analysis technique of Freddy Rangkuti through direct interviews with resource persons, namely farmer group II and also with the Focus Group Disscussion method. The strategy for certified community forest management in Dukuhdalem Village, Japara District, Kuningan Regency by the Mekarsaluyu II Farmer Group, obtained an IFAS value of -0,113 and an EFAS value of 0,133 and the right strategy in developing a certified community forest management strategy in Dukuhdalem Village, Japara District, Kuningan Regency by the Mekarsaluyu II Farmer Group is an Turn Around strategy.Permasalahan hutan rakyat bersertifikat adalah permasalahan pengelolaan, kebijakan pemerintah yang belum optimal mengenai hutan rakyat bersertifikat (Ada kebijakan P.85/Menlhk/Setjen/Kum.1/11/2016) Yang dulunya merupakan hutan rakyat bersertifikat hutan menjadi wajib sekarang bukan karena bagi hutan rakyat yang belum bersertifikat, mereka bisa menggunakan nota angkut untuk hasil kayunya), kelompok tani hutan bersertifikat kurang dalam mencari peluang, pengelolaan masih tradisional, dan adanya sertifikat tidak menjamin mudahnya penjualan. produk kayu mereka. Untuk itu metode yang digunakan dalam penelitian ini adalah dengan menggunakan teknik analisis SWOT dari Freddy Rangkuti melalui wawancara langsung dengan narasumber yaitu kelompok tani II dan juga dengan metode Focus Group Discussion. Strategi pengelolaan hutan rakyat bersertifikat di Desa Dukuhdalem Kecamatan Japara Kabupaten Kuningan oleh Kelompok Tani Mekarsaluyu II memperoleh nilai IFAS sebesar -0,113 dan nilai EFAS sebesar 0,133 serta strategi yang tepat dalam menyusun strategi pengelolaan hutan rakyat bersertifikat di Dukuhdalem Desa, Kecamatan Japara, Kabupaten Kuningan oleh Kelompok Tani Mekarsaluyu II merupakan strategi Turn Around .